Understanding public perception of bra size. Issue 11 (November 2022) - Malphrus, Elizabeth L.; Desai, Abhishek; Weiss, Eric S.; Couto, Javier A.; Broach, Robyn; Butler, Paris D.
Summary: Background: Breast cup size is often used in conversations between patients and their surgeons to communicate about goals and expectations for postoperative results. Cup size, however, is a poorly defined concept. The goal of this study was to assess whether the perception of breast cup size is consistent in a general population of survey respondents. Methods: A survey consisting of a demographic questionnaire, personal bra use questionnaire, and 27 de-identified preoperative images of patient's breasts was administered to 500 respondents using the Amazon MTurk platform. Survey respondents were asked to guess the cup size for each of 27 patients. Results: On average, respondents correctly identified the patient's reported cup size 43.32% of the time. Male and female respondents chose the same cup size for most breast images. Survey respondents who had professional fittings were significantly less likely to accurately identify cup size (38.75% vs. 42.67%, p  = 0.02). Those who had a personal history of breast surgery were also less likely to choose correctly (36.92% vs. 43.86%, p  < 0.01). Conclusion: The results of this study suggest that the perception of cup size is broadly similar across a general population sample. However, subgroups who would be expected to have more knowledge about and experience with breast sizing—including women who have had professional bra fittings and women who have had breast surgery—differ significantly in their perception of cup size. This suggests that cup size language should be used with caution in preoperative discussions between patients and their surgeons.